Pemberdayaan Perempuan Dalam Mewujudkan Ketahanan Pangan Rumah Tangga Melalui Kelompok Wanita Tani di Kecamatan Mamuju Kabupaten Mamuju - Teddu, Sulaiman; Ridwan; Ahmad, Ahfandi (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2023)
This research aims to know the empowerment of women in Women Farmers Group (KWT) as an effort to realize Household Food Security in Mamuju Sub-district of Mamuju Regency and to examine the impact of women in Women Farmers Group (KWT) on Household Food Security in Mamuju Sub-district of Mamuju Regency. The research was conducted for 3 months, from July to August 2017. Places of study are planned in the Mamuju sub-district of Mamuju Regency. The population is a Women Farmers group (KWT) in the Mamuju Sub-district of Mamuju Regency. As many as 10 Women Farmers Group samplings were done using the Simple Random Sampling method. Where the number of members of each group of women farmers was an average of 25 people, each group was selected as a sample of 10%. Thus, based on the population of 250 people, the samples were taken from as many as 25 people. For qualitative data, informants (Key and Main) are determined by purposive sampling, considering that the informant can provide in-depth information related to the research purpose because they are involved and know the information. Research shows that Women's Empowerment in the Farmers' Women Group as an effort to realize Household Food Security, among others: a) development in the form of training, which is an appropriate technology training based on local wisdom, counseling carried out by both the Farmer Women Group independently and the routine activities of the Mamuju District Agricultural extension center, and socialization to provide information in the form of the latest innovations and about new policies or programs from the government. b) Strengthening potential/power in the form of savings and loan activities to contribute to family resilience, especially in food security, Agricultural Product Processing Business as an effort to increase family income, and Utilization of the Yard as an effort to provide various foodstuffs themselves and as a living granary, a living pharmacy, as well as family savings and enhancers of beauty. 2) Women's empowerment in the Women Farmers Group in Mamuju Subdistrict, Mamuju Regency, impacts food security with 3 (three) aspects, namely: food availability, access, and utilization.